Extremal properties of linear dynamic systems controlled by Dirac`s impulse - Białas, Stanisław; Górecki, Henryk (1927-2022); Zaczyk, Mieczysław (Zielona Góra: Uniwersytet Zielonogórski)
The paper concerns the properties of linear dynamical systems described by linear differential equations, excited by the Dirac delta function.
Keywords: extremal properties; Dirac`s impulse; linear systems; transfer function